2017
DOI: 10.1158/1078-0432.ccr-16-3273
|View full text |Cite
|
Sign up to set email alerts
|

Acquired MET Y1248H and D1246N Mutations Mediate Resistance to MET Inhibitors in Non–Small Cell Lung Cancer

Abstract: amplification, responsible for 20% of acquired resistance to EGFR tyrosine kinase inhibitor (TKI) in patients with advanced non-small cell lung cancer (NSCLC), presents an attractive target. Numerous studies have conferred susceptibility of mutations and focal amplification to targeted MET-TKIs. However, the mechanism underlying MET-TKIs-induced resistance remains elusive. We conducted a cohort of 12 patients with advanced NSCLC who developed resistance to a combinatorial therapy consisting of gefitinib and a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 23 publications
(33 reference statements)
1
64
0
Order By: Relevance
“…Uncontrolled activation of c‐Met, such as c‐Met and HGF amplification or mutation, has been reported as an important cause of acquired resistance of NSCLC to EGFR‐TKI and is correlated with poor clinical outcomes . When binding to the receptor of c‐Met, HGF can phosphorylate c‐Met tyrosine kinase and subsequently activate the downstream ERBB3/PI3K/Akt signaling pathway, which promotes cell proliferation, migration, survival, and anti‐apoptosis effects . Moreover, c‐Met overexpression is also detected in NSCLC without EGFR‐TKI treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled activation of c‐Met, such as c‐Met and HGF amplification or mutation, has been reported as an important cause of acquired resistance of NSCLC to EGFR‐TKI and is correlated with poor clinical outcomes . When binding to the receptor of c‐Met, HGF can phosphorylate c‐Met tyrosine kinase and subsequently activate the downstream ERBB3/PI3K/Akt signaling pathway, which promotes cell proliferation, migration, survival, and anti‐apoptosis effects . Moreover, c‐Met overexpression is also detected in NSCLC without EGFR‐TKI treatment .…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of patients with crizotinib eventually leads to resistant mutations ( Figure 1F). Two mutations in the A loop D1246H/N [141][142][143][144][145] and Y1248H/C/S [141,[144][145][146] stabilize the active conformation of the A loop and decreases the efficacy of the drug [147]. At least one study identified the G1181R in addition to the Y1248 and D1246 mutations when an exon 14 skipping patient was treated with crizotinib [145].…”
Section: Hepatocyte Growth Factor Receptor (Hfgr C-met)mentioning
confidence: 99%
“…Resistance mutations to capmatinib arise that disrupt the interaction of the drug with the kinase. Patients with MET amplification treated with gefitinib and capmatinib developed the D1246N and the Y1248H resistant mutations [144]. Molecular modeling showed that the mutant c-MET was sufficiently distorted to prohibit the binding of the drug.…”
Section: Hepatocyte Growth Factor Receptor (Hfgr C-met)mentioning
confidence: 99%
“…In a recent study, Li et al (86) reported two acquired MET mutations, Y1248H and D1246N, which can cause resistance against Type I MET-TKIs. It was also noted that EGFR amplification may act as an alternative METTKIs bypass resistance mechanism (86). Amplification of MET, amplification of K-RAS and activation of B-RAF or EGFR pathways have also been proposed as mechanisms of acquired resistance to MET TKIs (87)(88)(89).…”
Section: Metmentioning
confidence: 99%